Length dependence of the number of phase slip lines in a superconducting strip - Aguirre, C. A.; Sardella, E. [UNESP]; Barba-Ortega, J. (Elsevier B.V., 2020)
We study the superconducting state of a strip under an transport current J(a) and an external magnetic field H. We show that the value of the critical currents at which the vortex-antivortex (V-Av) pair penetrates the sample, the number of phase-slip lines, and their average velocities and dynamics strongly depend on the size of the sample L. Our investigation was carried out by numerically solving the two-dimensional generalized time-dependent Ginzburg-Landau equations (GTDGL).
Keywords: Ginzburg-Landau; Anti-vortex; Mesoscopics; Superconductor; Phase slip lines